Fostering a prevention mindset for responsible gene editing. (19th May 2019) - Meagher, Karen M.; Master, Zubin
ABSTRACT: In this special issue, we solicited three commentators to discuss issues specific to the responsible conduct of research as it relates to the birth of gene-edited children. We explore the ethics of prevention and its ties to the responsible conduct of gene-editing research to introduce three commentaries addressing: (1) the relevance of cultural and regulatory context in China, (2) how to actualize calls for greater public engagement, and (3) where we might improve graduate education of genomic researchers.